High-resolution melting analysis based on specific genomic regions: A promising tool for the diagnosis and typing of species causing cutaneous leishmaniasis in Colombia - Johana Marin; Daniel Urrea; Carlos Muskus; María Clara Echeverry; Ana María Mejía; Omar Triana (Biomédica, 2017)
Introduction: Cutaneous leishmaniasis, caused by parasites of the genus Leishmania, is a disease with high incidence in Colombia. The diagnosis and identification of the infectious species are critical factors when selecting and initiating treatment. Currently, the methods for diagnosing and typing cutaneous leishmaniasis require complicated procedures and there is a need for the validation of new molecular markers and methods to simplify the process. Objective: To develop a tool based in PCR melting curves (PCR-HRM) for the diagnosis and typing of the three Leishmania species of epidemiological importance for cutaneous leishmaniasis in Colombia. Materials and methods: The genomes of Leishmania panamensis, L. braziliensis and L. guyanensis were compared with bioinformatic methods. The species-specific regions were then validated using PCR. For the selected markers, a PCR-HRM was designed, and validity and security parameters were estimated using isolates from Colombian patients previously characterized by PCR-RFLP of the hsp70 gene. Results: The comparative genomic analysis yielded 24 species-specific regions. However, the PCR validation identified only one marker that was specific to each Leishmania species. The other markers showed cross amplification. The detection limit for the three selected markers was one parasite. The sensitivity, specificity, predictive positive and negative values were 91.4%, 100%, 100% and 75%, respectively. Conclusions: The three selected regions can be used as molecular markers in the diagnosis and typing of the causative species of cutaneous leishmaniasis in Colombia.